Clinical challenges treating Stenotrophomonas maltophilia infections: an update. Issue 3 (5th May 2022) - Mojica, Maria F.; Humphries, Romney; Lipuma, John J.; Mathers, Amy J.; Rao, Gauri G.; Shelburne, Samuel A.; Fouts, Derrick E.; Van Duin, David; Bonomo, Robert A.
Abstract: Stenotrophomonas maltophilia is a non-fermenting, Gram-negative bacillus that has emerged as an opportunistic nosocomial pathogen. Its intrinsic multidrug resistance makes treating infections caused by S. maltophilia a great clinical challenge. Clinical management is further complicated by its molecular heterogeneity that is reflected in the uneven distribution of antibiotic resistance and virulence determinants among different strains, the shortcomings of available antimicrobial susceptibility tests and the lack of standardized breakpoints for the handful of antibiotics with in vitro activity against this microorganism. Herein, we provide an update on the most recent literature concerning these issues, emphasizing the impact they have on clinical management of S. maltophilia infections.